Selenium and high dose vitamin E administration protects cisplatin-induced oxidative damage to renal, liver and lens tissues in rats - Naziroglu, M; Karaoglu, A; Aksoy, AO (Elsevier Ireland Ltd, 2004)
Cisplatin is one of the most active cytotoxic agents in the treatment of cancer but its clinical use is associated with nephrotoxicity. Several studies suggest that supplementation with antioxidant can influence cisplatin induced nephrotoxicity. In the present study, we investigated the effect of selenium with high dose vitamin E administration on lipid peroxidation (MDA) and scavenging enzyme activity in kidneys, liver and lens of cisplatin-induced toxicity in rats. Forty female Wistar rats were used. They were randomly divided into five groups. The first and second groups were used as control and cisplatin (6 mg/kg BW) intraperitoneally administrated groups. Groups III, IV and V received intraperitoneally five doses of selenium (1.5 mg/kg BW) and a high dose of vitamin E (1000 mg/kg BW) combination before, simultaneously and after with cisplatin, respectively. Glutathione peroxidase (GSH-Px), vitamin E and P-carotene levels in the kidney, lens and liver, vitamin A and reduced glutathione (GSH) levels in the kidney were significantly (P <0.05 to <0.001) lower in the cisplatin group than in the control whereas there was a significant increase in kidney, liver and lens MDA levels in rats treated with cisplatin. The decreased antioxidant enzymes and vitamins and increased MDA levels in the kidney, lens and liver of animals administered with cisplatin were significantly (P <0.05 to <0.001) improved with selenium and a high dose vitamin E injection. In conclusion, this data demonstrates that there is an increase in lipid peroxidation in the kidney, liver and lens of animals administered with cisplatin whereas there is a decrease in antioxidant vitamins and enzymes. However, intraperitoneally injected selenium combined with a high dose of vitamin E seem to produce a significant improvement on antioxidants concentrations in rats treated before, simultaneously and after with cisplatin. The selenium with high dose vitamin E injection may play a role in preventing cisplatin-induced nephropathy and cataract formation in cancer patient. (C) 2003 Elsevier Ireland Ltd. All rights reserved.
Keywords: oxidative stress; cisplatin-nephrotoxicity; lens; liver; selenium; vitamin E